Sistem Informasi Inventory Barang Berbasis Aplikasi Mobile Web Untuk Koperasi: Study Kasus: Koperasi Konsumen Primer Sumber Daya Mandiri - Burhan Firdaus; Anang Jumardi; Muhamad Adin Wahyudin; Wasis Haryono (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Structured and efficient inventory management is very important for cooperatives, which have special operational and logistical needs. This study aims to develop a web-based inventory system and also develop it into a mobile application that is able to support real-time stock and asset management, using Javascript, PHP, HTML, CSS, and implemented on the XAMPP platform with phpMyAdmin support. This system is designed to record and monitor goods accurately, optimize the flow of goods in and out, and provide automatic inventory reports. The waterfall approach is applied in the development of this system, starting from needs analysis, design, implementation, to testing. The results of the study show that this system has succeeded in increasing the accuracy of recording goods, accelerating the decision-making process through data-based reports, and reducing manual errors that often occur in inventory management. This system not only supports operational transparency, but also helps a cooperative in achieving logistical efficiency and resource optimization.